1982
DOI: 10.1099/0022-1317-58-2-251
|View full text |Cite
|
Sign up to set email alerts
|

The Surface Antigens of Orthopoxviruses Detected by Cross-neutralization Tests on Cross-absorbed Antisera

Abstract: SUMMARYCross-neutralization tests were done on accepted species and recently isolated members of the genus Orthopoxvirus using antisera which had been separately absorbed with the various viruses. The results provided evidence for the involvement of four neutralizing antigens, and their distribution among 13 virus strains was determined. Monkeypox (Congo-8-Lombe), camelpox (Gorgan), ectromelia (Mill Hill), 'Lenny' and elephant poxviruses had distinctive antigenic formulae. Lister and Wyeth vaccines were indist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…This single direction of cross-neutralization suggests that ERPV has several neutralizing antigenic epitopes, only some of which are shared with vaccinia virus and ectromelia virus. Similar results are reported in other Orthopoxvirus cross-neutralization studies (Baxby, 1982).…”
Section: Discussionsupporting
confidence: 92%
“…This single direction of cross-neutralization suggests that ERPV has several neutralizing antigenic epitopes, only some of which are shared with vaccinia virus and ectromelia virus. Similar results are reported in other Orthopoxvirus cross-neutralization studies (Baxby, 1982).…”
Section: Discussionsupporting
confidence: 92%
“…Abs in VIG recognize many antigen targets, including surface proteins of both EV and MV virion forms of VACV (Davies et al, 2005a). Study of polyclonal Abs in poxvirus-immune sera of rabbits revealed the pattern of recognition for each poxvirus was unique, but also suggested that different poxvirus species shared common neutralizing determinants (Baxby, 1982). Studies in murine infection models identified targets for neutralizing and protective mouse monoclonal Abs (mAbs), which included the MV surface proteins A27, L1, H3, D8, A28, A13 and A17, and the EV surface proteins B5 and A33 (Moss, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A relatively large number of serological diagnostic approaches have been used to identify orthopoxvirus infection, including hemagluttination inhibition ( Jezek et al 1987a), gel precipitation (Gispen 1955;, complement fixation , cross-neutralization (Baxby 1982), immunofluorescence (Gispen et al , 1976, Western blot (Demkowicz et al 1992;Jones-Trower et al 2005;Dubois and Slifka 2008), radioimmunoassay/ELISA (Hutchinson et al 1977;Marennikova et al 1981;Jezek et al 1987a;Karem et al 2005;Hammarlund et al 2005), or a modified post-adsorption ELISA (Dubois and Slifka 2008). Of these serological approaches, the ELISA technique is the least labor intensive and most likely to be amenable to high-throughput quantitative analysis.…”
Section: Introductionmentioning
confidence: 99%